2010
DOI: 10.1677/joe-10-0015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding level on serum IGF1 response to GH injection

Abstract: This study was conducted to further understand the mechanism by which nutrition modulates GH-induced changes in serum IGF1 concentration in cattle. Cows were fed hay only or corn-based concentrates in addition to hay for 8 weeks. At week 8, serum concentrations of IGF1, IGF-binding protein 3 (IGFBP3), and acid-labile subunit (ALS) as well as their mRNA levels in liver were determined immediately before and 7 days after an injection of GH formulated for sustained release. GH injection caused greater increases i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…The concentrations at which IGF1 increased competence for development to the blastocysts stage in the present study is within the range of those found in the blood of lactating and non-lactating cows [26,27]. Surprisingly, IGF1 was more effective at increasing development at 100 ng/mL than at 200 ng/mL.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The concentrations at which IGF1 increased competence for development to the blastocysts stage in the present study is within the range of those found in the blood of lactating and non-lactating cows [26,27]. Surprisingly, IGF1 was more effective at increasing development at 100 ng/mL than at 200 ng/mL.…”
Section: Discussionsupporting
confidence: 77%
“…Concentrations were chosen so that the second concentration was within the range of values for IGF1 in blood of lactating cows [26,27]. The percentage of oocytes that cleaved (≥2 cell) was observed at Day 3 after insemination (~72 h post-insemination) and the percentage of embryos that became blastocyst was observed at Day 7 (168 h) and Day 8 (192 h) post-insemination.…”
Section: Concentration-dependent Actions Of Igf1 To Increase Blastocymentioning
confidence: 99%
“…Epidemiological studies indicate that a high concentration of blood‐circulating IGF1 is a strong risk factor of various cancers including colon cancer, 10 prostate cancer 11 and breast cancer, 12 while a low concentration of blood IGF1 is related to a number of metabolic diseases, such as diabetes mellitus 13 . Although the level of circulating IGF1 is affected by various factors including growth hormone concentration, 14 IGFBP concentration, 15 gender, 16 age, 17 ethnic group 18 and nutritional status, 19 twin studies have demonstrated that 38% of the variance of IGF1 concentration between individuals is contributed by genetic effects 20 . Recently, an association study using tagSNPs covering the IGF1 gene in a cohort of 450 middle‐aged men and women revealed that tagSNPs accounted for 2·1% of population variance of circulating IGF1 concentration 20 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been documented that the IGF system plays an important role in cell growth, differentiation, and mediation of growth hormone (Daughaday et al, 1989, Wu et al, 2010. Circulating IGF-I is linked to four IGF binding proteins (IGFBP-2, 3, 4 and 5; Silva et al 2009) that regulate its bioavailability.…”
Section: Discussionmentioning
confidence: 99%